Effect of Supplementation of Multi Enzymes on Production Performance and Egg Quality Traits in White Leghorn Layers - Pandian, C.; Sundaresan, A.; Omprakash, A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was conducted to assess the effect of supplementation of Multi-enzymes with lysophospholipids on production performance of pure line White Leghorn layers. Body weights before and after the experiment did not differ significantly across the experimental diets. Irrespective of the dietary treatments, the birds gained 3.83 per cent of live weight relative to its initial body weight. Mean per cent Hen housed egg production was significantly (P<0.05) higher in diet supplemented with 0.10 MEC-L than other groups. Mean egg weight and average daily feed consumption during 25 to 35 weeks of age indicated no significant effect of enzyme supplementation. Average daily feed consumption per bird in control, 0.05 % and 0.1 % multi-enzyme supplemented groups was 108.13, 105.66 and 107.67 g respectively and birds offered control diet recorded numerically more feed intake than enzyme supplemented groups. Comparatively low feed per egg was observed in 0.1 O per cent group followed by 0.05 per cent group which offers economic benefits than control diets. However, the egg quality traits between different dietary enzyme supplementation groups showed no significant difference.